Role of intrathecal and topical vancomycin in prevention of ventriculoperitoneal shunt infections - Tanweer Ahmed; Rabail Akbar; Anas Ahmed; Sana Akbar; Lal Rehman; Amjad Ali (Romanian Neurosurgery, 2023)
The objective of this study is to assess the role of intrathecal and topical vancomycin in the prevention of ventriculoperitoneal shunt infection. Infections of the ventriculoperitoneal (VP) shunt are a frequent consequence of shunt surgery. Different strategies, and protocols in addition to prophylactic intravenous antibiotic administration have been described to limit the infection rate, but the burden still remains high. The use of intrathecal Vancomycin along with topical application can be implemented as an additional measure to limit shunt-related infections.